Parental Responsibility - Katrin Bain (Social Work and Society)
Parental responsibility can be broadly defined as a legal term that specifies rights and responsibilities of parents towards their children. It is usually given initially to the birth mother and the married father, though unmarried fathers can obtain it either with the agreement of the mother or through a court order. In accordance with the provisions in law the court can also transfer parental responsibility to other persons (e.g. adoptive parents) or in cases of child abuse or neglect to the state, represented by local authority social services. While the concept of parental responsibility can be found in most countries, the exact terminology varies from one country to another, as well as over time.